Developing Computer-based Educational Game to support Cooperative Learning Strategy - Handriyantini, Eva (PROCEEDING IC-ITECHS 2014, 2014)
Game is one of learning media which can be used as a part of learning strategy inschool nowadays. Learning strategy using game can be more effective for students especially for developing mathematical skills of primary school students. Educational game development can use Waterfalls model, where development phases can be adjusted to be in accordance with the development needs of educational games. Educational games have teaching material therefore they can be used to support learning strategy in classroom.